Pengembangan Film Kartun Untuk Meningkatkan Kemampuan Representasi Matematis Siswa Pada Kurikulum Merdeka - maria, meisy sella; T, Ahmad Yani (Journal of Educational Review and Research, 2024)
The development of the education curriculum in Indonesia, especially the 2021 Merdeka Curriculum, focuses on cultivating character education through P5 (Strengthening Pancasila Student Profile Project). However, students still have difficulty understanding mathematics, especially mathematical representations. The aim of this research is to determine the development of cartoon films to improve students' mathematical representation abilities in the independent curriculum. The research uses development methods to analyze the development of cartoon films to improve mathematical representation abilities in the independent curriculum. The subjects studied in class IX A were 17 students. Data was obtained from observations, representation ability tests, and student interviews. The results show that the majority of students have moderate mathematical representation abilities with cartoon films playing an important role in improving representation abilities through active interaction. Low ability students need a deep approach and social support. Interviews showed positive changes in learning, but according to observations, some students were not active in the learning process. The goals of the Independent Curriculum have not been fully achieved. The results of teacher interviews revealed barriers to development, such as choosing a learning model according to the child's learning style. Teachers try to overcome this obstacle through reflection and discussion with fellow teachers as well as creating more interesting learning media such as cartoon films.